Penerapan Algoritma Venigmare Cipher dan Vernam Cipher Dalam Pengamanan Data Teks - Kermanosiavic Noverdianto Siahaan; Mesran Mesran (Universitas Budi Darma, 2020)
Data security and confidentiality is one very important aspect in today's information system. The emergence of internet and multimedia technology has prompted various efforts to protect, secure, and hide data on digital files from unauthorized parties to access these files. One of the efforts to secure data and information includes using the Venigmare Cihper and the Vernam Cihper. Venigmare is an encryption that can reduce the correlation between the frequency of letters in plaintext and Ciphertext. But unfortunately this method still leaves a repeating pattern, especially if the encrypted plaintext is long enough. In this case, the role of the data encryption technique known as cryptography is very important. Cryptography is a technique for encoding data through a process of encryption and decryption with a specific key to produce encrypted data that is unknown to others. This paper will use the Vernam Cipher algorithm.